The compared practice of the professional secret of journalists: Su relación con España - Barberá González, Rafael (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The journalist's professional secrecy in Spain finds its welcome in the 1978 Constitution. In this matter, as in many others, the Spanish situation must be compared with that of countries in our geographical-political environment. Carrying out an analysis of the realities in this matter offers us a common denominator, which is that Spain is not the only country in which the legislative development of professional secrecy is not very explicit. To understand this situation, it is convenient to focus on what the Constitution establishes to assess its content and the limits it offers.